The Effect of Self-Efficacy on Readiness to Become a Social Science (IPS) Teacher of Economic Education Students at State Universities in Pekanbaru City - Riyantama Isjoni, M. Yogi; Nurdiansyah; Syafriafdi, Non; Akmal, Atqo; Rizka, Mifta; Sintia, Apen (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study is to determine how self-efficacy affects career readiness to become a teacher. Using a quantitative approach and the sample is Social Sciences (IPS) students in the Economics education study program of state universities in Pekanbaru City, namely Riau University and Sultan Syarif Kasim State Islamic University totaling 170 students who have been determined by purposive random sampling technique using the slovin formula. The Likert questionnaire was used to collect data while simple linear regression analysis was used to analyze the data. The prerequisite test includes the normality test and the linearity test. The results of the analysis requirement test show that the data is normally distributed and has a linear relationship. Based on the simple linear regression test, it shows that self-efficacy has a positive and significant effect on readiness to become a teacher. The conclusion of this study is that there is a positive and significant effect of self-efficacy on readiness to become a teacher, meaning that students need to have a sense of confidence in themselves that they are able to carry out and complete the obligations faced, handle every challenge and can achieve the desired target when becoming a teacher